Improving Reading Comprehension Of The Eighth Grade Students At SMP Saraswati Tolai Through Skimming Strategy - Made Rani Arpiani; Rofiqoh Rofiqoh; Mashuri Mashuri; Afrillia Anggreni (Universitas PGRI Sumatera Barat, 2025)
The objective of this research is to prove the whether or not the use of skimming stategy improve the reading comprehension of grade eight students at SMP Saraswati Tolai. This research applied a quasi-experimental research design. The population of this research was grade eight students of SMP Saraswati Tolai. The sample of this research was selected by using purposive random sampling technique. The sample were class VIII A as the experimental group and class VIII B as the control group. These groups were given pre-test and post-test. The data were analyzed statistically in order to know the significant difference of the pre-test and post-test. The result showed the students' mean score of the experimental group on the pre-test and post-test are 39.35 and 50.53. The students' mean score of the control group on pre-test and post-test are 40.10 and 44.78. Consulting to the t- table value by applying degree of freedom (df) (31+32-2= 61) and 0.05 level of significance, the researcher found that the value of t-counted (8.94) is higher than t-table (2.005) causing the hypothesis accepted. It means that the implementation of skimming technique can significantly improve reading comprehension of grade eight students at SMP Saraswati Tolai. Keywords: improve reading comprehension, descriptive text, skimming strategy.